MALDI–MSI Pilot Study Highlights Glomerular Deposits of Macrophage Migration Inhibitory Factor as a Possible Indicator of Response to Therapy in Membranous Nephropathy. Issue 3 (22nd November 2018) - L'Imperio, Vincenzo; Smith, Andrew; Ajello, Elena; Piga, Isabella; Stella, Martina; Denti, Vanna; Tettamanti, Silvia; Sinico, Renato Alberto; Pieruzzi, Federico; Garozzo, Maurizio; Vischini, Gisella; Nebuloni, Manuela; et al.
Abstract : Purpose: Membranous nephropathy (MN) is the most frequent cause of nephrotic syndrome in adults and the disease course is characterized by the "rule of third", with one‐third of patients experiencing complete remission and the remaining experiencing relapses or progression of the disease. Additionally, the therapeutic approach is not standardized, leading to further heterogeneity in terms of response and outcome. Experimental design: In this pilot study, MALDI–MSI analysis is performed on renal biopsies ( n = 13) obtained from two homogeneous groups of patients, which differentially responded to the immunosuppressive treatments (Ponticelli regimen). Results: A signal at m/z 1303 displays the greatest discriminatory power when comparing the two groups and is observed to be of higher intensity in the glomeruli of the non‐responding patients. The corresponding tryptic peptide is identified as macrophage migration inhibitory factor (MIF). Conclusions and clinical relevance: Despite much effort being made in recent years to understand the pathogenesis of MN, a biomarker able to predict the outcome of these patients following therapeutic treatment is still lacking. Here, a protein (MIF), verified by immunohistochemistry, that can differentiate between these MN patients and could be a valuable starting point for a further study focused on verifying its predictive role in therapy response is highlighted.